Prototype Engine Cut Off System For Safety Driving Motorcycles Based IoT - Hadi, Ahmad Danang (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2023)
The safety system for driving a motorbike is a very important aspect to protect riders and other road users. In this research, we developed a safety system when the slope of a motorbik e exceeds the maximum limit to improve driving safety.The purpose of this study is to implement an ECO system that is able to disconnect motorcycle engine power automatically in emergency situations as a safety function, and besides that it can also send warning notifications via telegram messages for help to riders as a monitoring function.Through testing and evaluation, the test results of the tool show stability because from 0 ° to - 70 ° tilt to the left and 0 ° to 70 ° tilt to the right, with an average error of consecutive readings ranging from 0.189 ° to - 0.911 °. The largest percentage of reading error is also found in the measurement of 30° and 10° right tilt, which is -3%. Small variations between sequential readings are still within tolerance limits.The tilt detection speed of the motor is carried out quick ly and consistently within 0.1 seconds. The speed of time when sending notifications to telegram bots ranges from 7.23 seconds to 21.74 seconds the speed of sending depends on the hotspot internet signal, with the test results the prototype of the ECO system has proven effective in improving the safety of motorists and road users.